2007
DOI: 10.1086/519681
|View full text |Cite
|
Sign up to set email alerts
|

An X‐Ray Imaging Study of the Stellar Population in RCW 49

Abstract: We present the results of a high-resolution X-ray imaging study of the stellar population in the Galactic massive star-forming region RCW 49 and its central OB association Westerlund 2. We obtained a $40 ks X-ray image of a $17 0 ; 17 0 field using the Chandra X-Ray Observatory and deep NIR images using the Infrared Survey Facility in a concentric $8:3 0 ; 8:3 0 region. We detected 468 X-ray sources and identified optical, NIR, and Spitzer MIR counterparts for 379 of them. The unprecedented spatial resolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 76 publications
1
41
0
1
Order By: Relevance
“…We assume that the giant HII region RCW49 of size 100 pc is the structure blown by Westerlund 2. Tsujimoto et al (2007) provided a spectral fit of the diffuse X-ray emission from RCW49, from which we deduce a density ∼1.5 × 10 −3 cm −3 . We note that Westerlund 2 was detected by HESS (Aharonian et al 2007).…”
Section: Galaxymentioning
confidence: 95%
“…We assume that the giant HII region RCW49 of size 100 pc is the structure blown by Westerlund 2. Tsujimoto et al (2007) provided a spectral fit of the diffuse X-ray emission from RCW49, from which we deduce a density ∼1.5 × 10 −3 cm −3 . We note that Westerlund 2 was detected by HESS (Aharonian et al 2007).…”
Section: Galaxymentioning
confidence: 95%
“…An X-ray source, CXOU J102302.8-574606.9 (Tsujimoto et al 2007), found in a 130 ks Chandra observation has been suggested as a potential counterpart, 8 apart from the Westerlund 2 core, and its relation to the stellar cluster thus remains unknown. A distance to CXOU J102302.8-574606.9 of >10 kpc was proposed based on the column density from Chandra observations (Dormody et al 2009).…”
Section: Hess J1023-575mentioning
confidence: 99%
“…Very recently, Tsujimoto et al (2007) identified 468 X-ray sources in Wd2 with Chandra and fit each of the stronger 230 of these with an optically thin thermal plasma (APEC) model to derive foreground N(H). The sources are spread over a cluster core radius of -, a good 6 7 match to the resolution of the CO data used here.…”
Section: Distancementioning
confidence: 99%